Mystery science theater 3000. Season 12, The gauntlet [videorecording (DVD)] - Hodgson, Joel, 1960- (Shout Factory, 2019)
Kinga Forrester has unveiled the latest innovation in movie riffing, the gauntlet. Can Jonah Heston, Tom Servo, Crow T. Robot, and Gypsy survive sitting through six cheesy movies in a row? Confronted with Kinga Forrester's choices in torturous films, they band together and ward off lunacy by continuously riffing on the movies in rapid-fire succession.